Education for a culture of peace in a gender perspective - Reardon, Betty (Paris : UNESCO Pub., 2001)
Education for a Culture of Peace in a Gender Perspective
Includes bibliographical references.
Keywords: Peace -- Study and teaching; Women and peace -- Study and teaching; Sex discrimination -- Study and teaching; Teachers -- Training of; International education